THE EFFECT OF VOLUNTARY DISCLOSURE UPON THE EARNINGS RESPONSE COEFFICIENT - Ridla Tsamrotul Fuady (The Accounting Journal of Binaniaga, 2017)
This research aims to examine the effect of voluntary disclosure by calculating the unexpected earnings and being measured thru the voluntary disclosure index upon the earning response coefficient measured by cumulative abnormal return and leverage, price to book value and the size of a company which is controlled variable. This research has been covering all the emitents on the Syariah Share Index which is the Jakarta Islamic Index (JII) registered at the Indonesia Stock Exchange (BEI) in 2014. The indicator of the voluntary disclosure has adopted the index of Global Reporting Initiative (GRI) G4 version (the newest) refers to 3 (three) selected main components which is the Economic performance, social and environment performance. Data collection method has applied a documentation study which is by studying the evident, scientific paper, article, journal and website relating to the research objects. The result of the research has indicated that an empiric study can not describe the effects of the voluntary disclosure upon the earning response coefficient (ERC). The same conclusion has been obtained regarding each kind of voluntary disclosure which is the voluntary disclosure related to the financial information and the voluntary disclosure related to the social and environment information.Keywords : Voluntary disclosure, earnings response coefficient, Jakarta Islamic Index.